Cultivation of microalgae in fluidized bed bioreactor: Impacts of light intensity and CO2 concentration - Rosli, S.S. (Institute of Physics Publishing, 2020)
Harvesting of suspended microalgae biomass will generally incur excessive time and intensive energy due to low biomass density. Microalgae cultivation via fluidized bed bioreactor was introduced to tackle the harvesting process in which the support material was fluidizing within the culture medium, allowing the microalgae to settle onto the surface of fluidized material and grow thereafter. The Central Composite Design (CCD) was adopted to design the experiments for optimization of attached microalgae growth onto the fluidized bioreactor. The optimization condition occurred at 216 Î¼mol/m2 s light intensity and 9 CO2 concentration with maximum biomass concentration (Xmax) and maximum specific growth rate Î¼max) of attached microalgae obtained at 0.692 g/L and 0.028 1/h, respectively. The Verhulst logistic kinetic model illustrated the attached microalgae growth from lag to stationary phase, supporting the use of this model to represent the kinetic of attached microalgae growth onto the fluidized bed bioreactor under various condition. Â© Published under licence by IOP Publishing Ltd.